Traumatic Abdominal Wall Hernia : A Johor Case Report - Lee, Yeong Ji; Yew, Ting Ting; Chan, Ai Chen (JOHOR STATE HEALTH DEPARTMENT, 2012)
Most reported cases of traumatic abdominal wall herniation result from blunt impact particularly handlebar injuries. The diagnosis is often made on physical examination or abdominal computed tomography (CT). We report a 22-year-old man with anterior abdominal wall swelling following blunt handle bar injury to the abdomen. This patient was initially thought to have an abdominal wall haematoma. However he developed symptoms of abdominal pain and vomiting 4 days later. An urgent CT was performed which confirmed the diagnosis of traumatic abdominal hernia. Intraoperatively, the herniated small bowel loops were gangrenous with multiple perforations leading to bowel contents contamination in the abdomen, chest and neck region. This case highlights the need for a high index of suspicion for traumatic herniation in patients who sustain low-velocity blunt abdominal wall trauma.